2020
DOI: 10.5334/jpl.240
|View full text |Cite
|
Sign up to set email alerts
|

Eyes or mouth? Exploring eye gaze patterns and their relation with early stress perception in European Portuguese

Abstract: Previous research has shown that eye gaze patterns relate to language development, with more attention to the mouth signaling ongoing acquisition. We examined infants' eye gaze in a stress perception experiment, in which European Portuguese (EP) learning infants showed a preference for the iambic stress pattern. Specifically, we asked whether there was a relation between eye gaze patterns and the preferred stress pattern. Eye gaze patterns of 25 monolingual typically developing infants aged 5-6 months old were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
3
5
0
Order By: Relevance
“…We observed that the two groups demonstrated certain similarities in their looking pattern: both groups do attend less to the waving arm at this age than the face and the background, suggesting that at this age the waiving gesture is not a particular salient communicative cue. Further, when attending to the face, both groups look more at the eyes than the mouth, in line with many recent studies done at similar ages (e.g., [ 41 , 42 , 43 ]). However, we observed a striking difference between the groups: TD infants attend more to the face than to the background, whereas DS infants attend similarly (~40 percent of their looking time to the screen) to the background and the face.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We observed that the two groups demonstrated certain similarities in their looking pattern: both groups do attend less to the waving arm at this age than the face and the background, suggesting that at this age the waiving gesture is not a particular salient communicative cue. Further, when attending to the face, both groups look more at the eyes than the mouth, in line with many recent studies done at similar ages (e.g., [ 41 , 42 , 43 ]). However, we observed a striking difference between the groups: TD infants attend more to the face than to the background, whereas DS infants attend similarly (~40 percent of their looking time to the screen) to the background and the face.…”
Section: Discussionsupporting
confidence: 89%
“…In particular, the richness of the interplay between the acoustic signal, articulatory movements and facial expressions is reduced in animated characters, in comparison to a human face. Interestingly, even with the animated character, DS and TD infants attend more to the eyes than the mouth, similar to previous studies assessing attention to a human face (e.g., [ 41 , 42 , 43 ]). Moreover, we also found that DS infants differ from TD infants in how they attend to communicative cues in an animated character talking face.…”
Section: Discussionsupporting
confidence: 85%
“…We observed that, depending on mask condition, the infants' looking patterns changed. In response to the face mask, the infants dominantly spent more time looking at the eyes, whereas, without the mask, the infants alternated between the eyes and the mouth (in line with Cruz et al, 2020 ; Pejovic et al, 2021 ; Sekiyama et al, 2021 ). This suggests that, when articulatory cues are occluded, infants do not attend to the occluded area but redirect their attention to the available visual cues, namely, those provided by the eyes.…”
Section: Discussionsupporting
confidence: 70%
“…During the 1st year of life, infants are dominantly exposed to human faces in comparison to other stimuli in their environment (Fausey et al, 2016 ; Jayaraman and Smith, 2018 ), and research has demonstrated infants' early sensitivity to visual speech (e.g., Kuhl and Meltzoff, 1984 ; Patterson and Werker, 1999 ; Lewkowicz and Hansen-Tift, 2012 ; Tomalski et al, 2013 ; Morin-Lessard et al, 2019 ; Pejovic et al, 2019 ). Such early sensitivity to visual speech has been proved important in infants' language development, namely, in language discrimination abilities (Weikum et al, 2007 ; Sebastián-Gallés et al, 2012 ), learning of phonemic contrasts (Teinonen et al, 2008 ), processing of stress (Cruz et al, 2020 ), and processing of familiar words (Weatherhead and White, 2017 ). When processing faces, infants dominantly attend to the eyes and the mouth of a speaker (e.g., Hunnius and Geuze, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation